Partisipasi Aparat Desa dalam Observasi Peta Kerawanan Bencana Longsor di Desa Ayuhulalo Kecamatan Tilamuta Kabupaten Boalemo - Daud Yusuf (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2023)
This activity was carried out to evaluate the existing flood hazard data in Boalemo Regency, especially in Ayuhulalo Village. The participation of local village officials is fully involved through several stages of activities. In the first stage, village officials were given socialization regarding the disaster hazard map in Boalemo Regency. The socialization is intended to provide an understanding of the map to village officials. In the second stage, village officials assisted by students were given knowledge about using the Avenza Map application. This application is then used for tracking to check the landslide disaster hazard map of Ayuhulalo Village